ANWAR IBRAHIM’S THE ASIAN RENAISSANCE REVISITED - Bakar, Osman; Moon, Ayana Jihye (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
Anwar’s The Asian Renaissance is an inspiring book with precious messages for our times that deserves to be read, especially by Asia’s younger generation. It is as relevant today as it was three decades ago. It is even more relevant today when the rise of Asia, especially as an economic power is becoming increasingly visible globally. It is therefore not surprising that China and South Korea are interested in translating Anwar’s The Asian Renaissance into their respective languages. Xiamen University China is to be congratulated for its laudable initiative in undertaking the translation of the original English edition of this book into Mandarin. Thanks to this translation, millions of Chinese-speaking readers, especially in China, can now benefit from this cogent discourse by a leading Asian intellectual and political leader on issues pertaining to the future of their respective countries and the common destiny of their continent. A Korean translation of the book is now under discussion. A new second edition of Anwar’s The Asian Renaissance would also be greatly welcomed by many people around the globe!